1996
DOI: 10.1207/s15327108ijap0602_4
|View full text |Cite
|
Sign up to set email alerts
|

On the Relation Between Personality and Job Performance of Airline Pilots

Abstract: The validity of a personality questionnaire for the prediction of job success of airline pilots is compared to validities of a simulator checkflight and of flying experience data. During selection, 274 pilots applying for employment with a European charter airline were examined with a multidimensional personality questionnaire (Temperature Structure Scales; TSS). Additionally, the applicants were graded in a simulator checkflight. On the basis of training records, the pilots were classified as performing at st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 6 publications
2
29
0
2
Order By: Relevance
“…The difference in the Agreeableness scale between the current study and Callister (1999) suggests that the training environment (civil or military) or the different selection criteria could be contributing factors, which calls for further studies. In terms of strong Conscientiousness, this study conforms to some previous studies which suggested higher levels of Conscientiousness (Fitzgibbons et al, 2004;Carretta et al, 2014), highly competitive (Picano, 1991;Callister, 1999) achievement striving (Hormann & Maschke, 1996;Callister, 1999;Lambirth et al, 2009) and highly motivated (Chidester et al, 1991) among the pilot population. Such finding supports the notion that pilot students are aware of the challenges to achieve success in aviation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The difference in the Agreeableness scale between the current study and Callister (1999) suggests that the training environment (civil or military) or the different selection criteria could be contributing factors, which calls for further studies. In terms of strong Conscientiousness, this study conforms to some previous studies which suggested higher levels of Conscientiousness (Fitzgibbons et al, 2004;Carretta et al, 2014), highly competitive (Picano, 1991;Callister, 1999) achievement striving (Hormann & Maschke, 1996;Callister, 1999;Lambirth et al, 2009) and highly motivated (Chidester et al, 1991) among the pilot population. Such finding supports the notion that pilot students are aware of the challenges to achieve success in aviation.…”
Section: Discussionsupporting
confidence: 90%
“…Hormann and Maschke (1996) used Temperament Structure Scales (TSS) and found airline pilots could be characterised by strong factors of sociability, well-balanced selfassertiveness and strong orientation towards actions and activity. Other personality traits included the need for mastery and expressivity along with low scores associated with arrogance and hostility.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The MMPI, MMPI-2, and the MCMI enabled the measurement of traits so findings could be validated by subsequent research. For example, research using instruments such as versions of the MMPI or the MCMI have resulted in descriptions of aviators as being "self-assertive," and "action oriented," with "high achievement needs," and "stable self-identity" (Hormann & Maschke, 1996;Shinar, 1995).…”
Section: The Aviator Personalitymentioning
confidence: 99%